Feasibility of Methylated CLIP4 in Stool for Early Detection of Colorectal Cancer: A Training Study in Chinese Population - Cao, Yang; Zhao, Guodong; Cao, Yaping; Chen, Zhiliang; Liu, Xiaoyu; Yuan, Mufa; Yang, Jun; Wang, Xiaomei; Ma, Yong; Liu, Zhaocheng; Xiong, Shangmin; Zheng, Minxue; et al. (Frontiers in Oncology, 2021)
Background: Early detection of colorectal cancer (CRC) and precancerous lesion is vitally important for mitigating CRC morbidity and mortality. Aberrant DNA methylations in certain promoter regions have been identified to be closely associated with CRC development and progression, suggesting their potential as diagnostic biomarkers for early detection. In this study, we evaluated the performance of methylated CLIP4 in stool specimens as a potential biomarker for CRC detection. Methods: A total of 321 subjects out of 365 enrolled participants were included in the final analysis, including 154 CRC patients, 23 advanced adenoma (AA) patients, 49 small polyp (SP) patients, and 95 healthy controls. CLIP4 methylation level was examined by qPCR with bisulfite converted DNA purified from approximately 5g stool specimen. Results: Methylated CLIP4 test showed high sensitivities of 78.3% (95% CI: 55.8% - 91.7%) and 90.3% (95% CI: 84.2% - 94.3%) for detecting AA and CRC, respectively, with a specificity of 88.4% (95% CI: 79.8% - 93.8%). CLIP4 methylation level discriminated AA and CRC patients from control subjects with area under the curve values of 0.892 (95% CI: 0.795-0.988) and 0.961 (95% CI: 0.938-0.983). Further analysis indicated no significant difference in sensitivities among different ages, genders, stages, locations, sides, tumor sizes and differentiation statuses. Conclusions: Methylated CLIP4 showed a strong potential as a noninvasive biomarker for early CRC detection.